The history of formation banking system in Islamic culture (Journal of Philosophy Culture and Political Science, 2019)
The article examines the history of Islamic banking. For a more detailed study the history of Islamic banks was reviewed from both the theoretical and practical sides. As well as this article deals with factors that contributed to development of Islamic banks as an alternative to classical Western banks. Based on this article, we can conclude that the main reason for the formation of Islamic banking system was the religious beliefs of the Muslim society. Because it is commonly known and acknowledged that Islam has strictly prohibited interest. It disapproves both giving and charging interest. Also, the article reveals the circumstances of the first Islamic banks that were created in the second half of the 20th century.Key words: Islamic bank, western banks, per cent, history, financial system.